Acrylamide based hydrogels in swelling and uptake of methylene blue from aqueous solutions - Kocabay, Ozlem Gokce; Ismail, Osman (SAGE PUBLICATIONS INC, 2020)
Several kinds of acrylamide-poly(ethylene glycol) hydrogels were synthesized at room temperature (25 degrees C) by adding N,N,N',N'-tetramethylethylenediamine crosslinker to AAm aqueous solutions containing 0, 0.20, 0.40, 0.60, 0.80 and 1 mg of PEG(6000). Water uptake and dye-sorption properties of the synthesized poly(acrylamide) and acrylamide-poly(ethylene glycol) hydrogels were investigated as a function of chemical composition of the hydrogels. Cationic dye (methylene blue) has been used in sorption studies. It was determined that poly(ethylene glycol) used for pore forming in synthesizing the hydrogel has an influence on the adsorption of methylene blue as in the case of adsorption phonemia. Adsorption equilibrium was investigated by using Langmuir and Freundlich isotherm models. Two kinetic models, (i) pseudo-first-order and (ii) pseudo-second-order kinetic models were applied to test the experimental data. Freundlich isotherm model represented the experimental data very well. Methylene blue adsorption followed the pseudo-second-order kinetic model which indicated chemical adsorption.
Keywords: Acrylamide; hydrogel; absorption; dye sorption; kinetic model; MACROPOROUS POLY(ACRYLAMIDE) HYDROGELS; ADSORPTION; SORPTION; REMOVAL; DYE; Chemistry